Emil Artin and Helmut Hasse: the Correspondence 1923-1958 - Frei, Günther; Lemmermeyer, Franz; Roquette, Peter (Springer Basel Imprint: Springer, 2014)
Part I: Introduction to the Correspondence -- 1. Introduction -- 2. Emil Artin, his Life and his Work -- 3. Reminiscing Helmut Hasse -- 4. Reciprocity Laws for Power Residues -- 5. Class Field Theory -- 6. Time Table -- Part II: The Letters. References -- Name Index -- Subject Index
Description based upon print version of record
Keywords: Briefsammlung; Hasse, Helmut; Artin, Emil